Transcriptome Response Mediated by Cold Stress in Lotus japonicus - Calzadilla, Pablo I.; Maiale, Santiago J.; Ruiz, Oscar A.; Escaray, Francisco J. (Frontiers in Plant Science, 2016)
Members of the Lotus genus are important as agricultural forage sources under marginal environmental conditions given their high nutritional value and tolerance of various abiotic stresses. However, their dry matter production is drastically reduced in cooler seasons, while their response to such conditions is not well studied. This paper analyzes cold acclimation of the genus by studying Lotus japonicus over a stress period of 24 h. High-throughput RNA sequencing was used to identify and classify 1077 differentially expressed genes, of which 713 were up-regulated and 364 were down-regulated. Up-regulated genes were principally related to lipid, cell wall, phenylpropanoid, sugar, and proline regulation, while down-regulated genes affected the photosynthetic process and chloroplast development. Together, a total of 41 cold-inducible transcription factors were identified, including members of the AP2/ERF, NAC, MYB, and WRKY families; two of them were described as putative novel transcription factors. Finally, DREB1/CBFs were described with respect to their cold stress expression profiles. This is the first transcriptome profiling of the model legume L. japonicus under cold stress. Data obtained may be useful in identifying candidate genes for breeding modified species of forage legumes that more readily acclimate to low temperatures